Aproximácie rozdelenia celkovej škody a ich aplikácia v interných aktuárskych modeloch - Páleš, Michal (Univerzita Pardubice, 2011)
Based on quality actuarial analysis of specific data, an effective method to estimate the distribution of total claim is chosen. Approximate, recurrent procedures and simulation techniques can be used, for example. This paper presents approximate the effect normal distribution compared with standard procedure. The entire sample is presented for calculating the risk premium for explicit examples including the use of computer technology.
Keywords: risk theory; individual risk model; normal approximation; lyapun characteristic; Berry-Esseen theorem; risk premium; central limit theorems